Dietary supplementation with l-glutamine and soluble fiberin refractory chronic diarrheain aids patient: a case report - Silva, Renata P; Costa, Paulla Suylane SF; Burgos, Maria Goretti PA (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Dietary supplementation of soluble fiber and L-glutamine has shown beneficial effects in refractory chronical diarrhea associated with aids. The aim of this study was to report the effect of supplementation in patients with refractory diarrhea associated with wasting of HIV/aids. Enteral nutritional therapy associated with L-glutamine and soluble fiber has been effective in controlling diarrhea, probably because of its assistance in the repair of the colonic mucosa, favoring the rapid intestinal recovery. The positive result achieved suggests a new protocol support in the treatment of refractory chronical diarrhea in these individuals.